2019
DOI: 10.1161/jaha.119.012436
|View full text |Cite
|
Sign up to set email alerts
|

Trace Minerals, Heavy Metals, and Preeclampsia: Findings from the Boston Birth Cohort

Abstract: BackgroundPreeclampsia is a leading contributor to maternal and perinatal morbidity and mortality. In mice experiments, manganese (Mn) and selenium (Se) are protective whereas cadmium (Cd) is promotive for preeclampsia. Epidemiologic findings on these chemical elements have been inconsistent. To confirm experimental findings in mice, we examined associations of trace minerals (Mn and Se) and heavy metals (Cd, lead [Pb], and mercury [Hg]) with preeclampsia in a birth cohort.Methods and ResultsA total of 1274 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 40 publications
2
49
2
2
Order By: Relevance
“…In adults, some studies suggested that Se and Mn may have protective effects against hypertension and CVD, although there is also evidence of possible adverse effects, nonlinear relationships, or null effects of these elements on BP and CVD (Bulka et al 2019;Laclaustra et al 2009; Lee and Kim 2011; Mordukhovich et al 2012;Nawrot et al 2007;Wu et al 2017). In pregnant women, we reported in the Boston Birth Cohort (Liu et al 2019) and in Project Viva (Liu et al 2020) that higher maternal Mn levels were prospectively associated with lower risk of preeclampsia, a pregnancy complication characterized by high BP and a known risk factor for child high BP (Zhang et al 2020b). It is unclear how in utero exposure to Se and Mn is associated with BP in children.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In adults, some studies suggested that Se and Mn may have protective effects against hypertension and CVD, although there is also evidence of possible adverse effects, nonlinear relationships, or null effects of these elements on BP and CVD (Bulka et al 2019;Laclaustra et al 2009; Lee and Kim 2011; Mordukhovich et al 2012;Nawrot et al 2007;Wu et al 2017). In pregnant women, we reported in the Boston Birth Cohort (Liu et al 2019) and in Project Viva (Liu et al 2020) that higher maternal Mn levels were prospectively associated with lower risk of preeclampsia, a pregnancy complication characterized by high BP and a known risk factor for child high BP (Zhang et al 2020b). It is unclear how in utero exposure to Se and Mn is associated with BP in children.…”
Section: Introductionmentioning
confidence: 66%
“…Lead (Pb), mercury (Hg), and cadmium (Cd) are highly toxic metals that have no known physiological role but can cause adverse health effects even at trace levels. Exposure to these metals is associated with higher risk of hypertension and CVD in adults (Chowdhury et al 2018;Hu et al 2018;Lanphear et al 2018;Navas-Acien et al 2007;Nawrot et al 2002) and in pregnant women (Kahn and Trasande 2018;Liu et al 2019). The prevalence of exposure to these metals among pregnant women is high.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there are several studies examining the association between cadmium exposure and preeclampsia in the United States. Liu et al 60 measured trace and toxic metals in a cohort of Boston women after delivery and found that each 1 standard deviation increment increase in cadmium in maternal red blood cells was associated with a 15% higher risk of preeclampsia. They also found that each 1 standard deviation increment in manganese was associated with a 32% lower risk of preeclampsia.…”
Section: Expert Reviewmentioning
confidence: 99%
“…They also found that each 1 standard deviation increment in manganese was associated with a 32% lower risk of preeclampsia. 60 Dawson et al 62 examined cadmium levels in the amniotic fluid from pregnancies complicated by preeclampsia and compared them with normotensive controls. Amniotic fluid cadmium levels were 18% higher in women with preeclampsia than normotensive controls.…”
Section: Expert Reviewmentioning
confidence: 99%
“…In addition, maternal exposure to toxic elements, such as mercury, cadmium, and lead, is also concerned [ 3 , 4 ]. In the vulnerable periods of pregnancy and lactation, deficiency and overload of essential trace elements as well as excessive accumulation of toxic elements might co-exist, likely increasing risks of maternal complications [ 5 , 6 ], stillbirth [ 7 ], birth defects [ 8 , 9 ], fetal growth restriction [ 10 , 11 , 12 ], or long-term low neurobehavioral functions [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%